Istratijiyah ta'lim maharah al kalam al iliktroniy fi al marhalah al jami'iyyah - Muh. Faruq; Abdul Muntaqim Al Anshory (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2022)
The Covid-19 pandemic has been affecting the education field so much that the educational process is changing to web-based instruction such as e-learning. The aim of this research is to describe the application of an e-learning strategy for speaking skill in the Arabic Language Center (PKPBA) Universitas Islam Negeri Maulana Malik Ibrahim Malang and the students' opinions about it. This research is descriptive qualitative research. Data sources are the process of teaching speaking skill in class 21 of the science and technology department and students. The data collection tools used are observation, interview and documentation. As for the method of data analysis, it is a method of analyzing qualitative data that consists of stages: data reduction, presentation, and conclusion. This study indicated that an e-learning strategy for speaking skill in the Arabic Language Center at Universitas Islam Negeri Maulana Malik Ibrahim Malang was applied by means of WhatsApp, YouTube, and Google Meet. The strategy consisted of actions: 1) Before education: preparing a WhatsApp group, giving study materials in the form of pdf and educational video on a YouTube link; 2) When teaching: sharing a Google Meet link, explaining new vocabulary or phrases, reading the exemplary dialogue text and students imitate it, several students practice the dialogue, giving students a chance to submit questions; 3) After education: evaluation through the application of dialogue between students and conclusion. As for the students, they see that this strategy is attractive and suitable for its application in teaching speaking skill, and it is effective in improving their speaking skill and motivation when learning.